Analisis wacana kritis Van Dijk pada pemberitaan media online Lampung “Manajemen konflik kasus kekerasan di UIN Raden Intan Lampung” - Ana Yunita, Ana Yunita Pratiwi; Siti Patimah; Rumadani Sagala (STIES ALIFA, 2021)
This study aims to describe the description of conflict management in cases of sexual violence at UIN Raden Intan Lampung by looking at how organizational leaders identify conflicts, factors that cause conflict, choose strategies in handling conflicts and the impact of conflicts in sexual violence cases. This research is qualitative research with data collection using the documentation of several local online media in Lampung. The results showed that organizational leaders identified sexual harassment conflicts as individual problems that developed into inter-organizational conflicts. The partisanship of the leadership of UIN Raden Intan Lampung on one of the conflicting parties triggered the latent conflict to be brought to the surface and led to an increase in the involvement of others. Cases of sexual harassment are related to situations of social injustice caused by gender differences. The conflict management approach is carried out with a strategy of calming (smoothing), accommodating, avoiding through top management communicators. Organizational rehabilitation efforts by establishing standard operating procedures for student services. Rehabilitation as social and mental reconciliation of female students who are victims has not been a concern in its management.